Interpretasi Laporan Keberlanjutan Pemerintah Daerah di Negara Berkembang: Pendekatan Filsafat - Aditiya, Roby; Habbe, Abdul Hamid; Pagalung, Gagaring (SUSTAINABLE, 2025)
Sustainability reporting in local governments in developing countries is an important concern in the discourse of responsible public governance. This study aims to examine the urgency of sustainability reporting in the public sector through a philosophical approach that includes the dimensions of ontology, epistemology, and axiology, with a focus on the context of Indonesia as a developing country. This research uses a qualitative literature study method with a scoping review approach of relevant international and national scientific articles, with analysis carried out thematically and philosophically to explore representations of reality, knowledge construction, and values that underlie local government sustainability reporting practices. The results of the study show that sustainability reporting practices in local governments in developing countries such as Indonesia are still in the normative stage and do not fully reflect the integration of substantive sustainability values. The reported reality is dominated by technocratic and symbolic narratives that do not fully represent social and ecological dynamics, while the knowledge formed tends to reproduce institutional structures without community involvement and local stakeholder participation. In addition, ethical values of sustainability have not been internalized in the reporting system, making reporting more of a bureaucratic formality than a public accountability tool. These findings emphasize the importance of transforming sustainability reporting into a participatory and value-based reflective space, with implications including the need for policy reform, strengthening institutional capacity, and community engagement in defining sustainability contextually.